Pesticide usage Behavior and Cholinesterase Blood Level of Farmers: Case Study of Latlumkaeo District, Pathumthani Province - วงศ์สกุลกาญจน์, วัชราภรณ์; มังกรทอง, ศิริศักดิ์; เที่ยงแท้, ประจวบลาภ (Ratchaphruek Journal, 2018)
ABSTRACT The research objective was to study relationship between personal factors, pesticide usage behavior and cholinesterase blood level of farmers at Latlumkaeo district, Pathumthani province. The tool used in the study; included (1) interview form and (2) cholinesterase test kit. Data was collected from 110 farmers. Data was analyzed by descriptive statistics such as frequency and percentage. The inferential statistic chi square test was used to analyze the factors, related to cholinesterase blood level of farmers. The results showed that 75.5 percent of pesticide usage behaviors were good, 21.8 percent and 2.7 percent were moderate and poor, respectively. Cholinesterase blood levels of 53.6 percent farmer were risk, 34.5 percent were unsafe but 11.8 percent were safe. Based on the hypothesis testing, sex and pesticide use duration had significantly effect with cholinesterase blood level of farmers (p-value <0.05).